Physicochemical characterization of calcium-doped barium zirconate perovskites for hydrogen-induced systems and their life cycle assessment - Yilmaz, Enes Emre; Kosma, Elvan Burcu; Figen, Halit Eren; Elibol, Meltem Karaismailoglu (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
BaZrO3 perovskites attract considerable attention in electrocatalytic applications. This study offers a comprehensive overview of synthesizing BaZrO3 perovskite material via the sol-gel method and investigates the impact of Ca-doping on its physicochemical properties. The hydrogen temperature-programmed reduction profiles and X-ray photoelectron spectroscopy analyses demonstrate that Ca-doping effectively enhanced the concentration of oxygen vacancies, which makes the material a candidate for hydrogen-induced electrocatalytic applications. Additionally, life cycle analysis results indicate the synthesis of Ba0.6Ca0.4ZrO3 perovskite with the most concentrated oxygen vacancies among synthesized perovskites caused the highest environmental impact, with marine and freshwater ecotoxicity being the primary environmental concern.
Keywords: Barium zirconate perovskite; Hydrogen reduction; Oxygen vacancies; Life cycle assessment; INDUSTRIAL-SCALE; MORPHOLOGY; CHEMISTRY; EVOLUTION; FRAMEWORK; PROTON; BAZRO3; STATE; Electrochemistry; Energy & Fuels